2003
DOI: 10.1097/01.asn.0000086475.83211.df
|View full text |Cite
|
Sign up to set email alerts
|

Improved Acidosis Correction and Recovery of Mesothelial Cell Mass with Neutral-pH Bicarbonate Dialysis Solution among Children Undergoing Automated Peritoneal Dialysis

Abstract: Abstract. Acid-base balance and peritoneal membrane longevity are of utmost relevance for pediatric patients undergoing peritoneal dialysis (PD). PD fluids with neutral pH and reduced glucose degradation product contents are considered more biocompatible, because they preserve peritoneal cell functions in vitro. To investigate the clinical effects of a novel PD fluid buffered with 34 mM pure bicarbonate at neutral pH, a randomized, prospective, crossover comparison with conventional, acidic, 35 mM lactate PD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 28 publications
3
95
0
3
Order By: Relevance
“…Additionally, we excluded two trials that did not meet our inclusion criteria. First, a study by Haas et al (26) was of pediatric patients, and thus, it was excluded on the basis of our inclusion criteria. Second, a randomized study conducted by Fan et al (27) was not included, because it reported only baseline measurements and the change in these measurements during the study period rather than final values.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we excluded two trials that did not meet our inclusion criteria. First, a study by Haas et al (26) was of pediatric patients, and thus, it was excluded on the basis of our inclusion criteria. Second, a randomized study conducted by Fan et al (27) was not included, because it reported only baseline measurements and the change in these measurements during the study period rather than final values.…”
Section: Discussionmentioning
confidence: 99%
“…The primary advantages of the bicarbonate-based solution are: (1) a physiologic pH; (2) a buffer that is physiologic in nature and at a physiologic concentration; (3) reduced GDPs; and (4) reduced lactate concentration. The bicarbonate buffered PD solutions have been shown to cause less peritoneal damage both in vitro and in vivo (75). In a crossover study of 12 stable PD patients who were switched to neutral pH, bicarbonate buffered solutions for 6 months, the level of CA125 at baseline was 15.07 Ϯ 5.72 U/ml, which after 6 months of treatment with bicarbonate PD solutions increased to 111.97 Ϯ 66.21 U/ml, whereas the mean values after the patients' return for another 6 months to the conventional solution use dropped again to 22.72 Ϯ 16.06 U/ml (76).…”
Section: Pd Solutions With Neutral Phmentioning
confidence: 99%
“…In contrast, data from randomized controlled trials (RCTs) are conflicting. Of the 13 RCTs that reported peritonitis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), only 2 showed significant benefit with the use of biocompatible PD solutions (19,22); the remainder reported a neutral effect. However, most trials examined peritonitis as a secondary outcome only; they can therefore not be regarded as providing definitive evidence.…”
Section: Introductionmentioning
confidence: 99%